(untitled) (Palimpsesto, 2017)
The following work aims to explore the representation or the self- representation’ of Mapuche people within the Chilean theatre. In order to do so, this paper explores the opportunities for the representation of Mapuches in national theatre and and the understanding made of it. This article provides a first revision of the activity of Conjunto Artístico Araucano Llefquhuenu in 1940 and some of the work produced by Isidora Aguirre (1919) and finally Ñi pu tremen by the director Paula González (1983).